The historical transformation of cultural journalism - Kristensen, Nete Nrgaard (Northern Lights: Film & Media Studies Yearbook, 2010)
This article is based on the first content analysis of the coverage of culture, lifestyle and consumption or journalism on culture in the Danish printed press during the twentieth century. It argues that cultural journalism has expanded and developed its focus, interpretation and presentation of culture concurrently with a changing culture and consumer industry and especially as part of, and a result of, an increasingly competitive and professionalized media landscape. This should be seen in the light of a culturalized and mediatized society: the media (in this case the newspapers analysed and their coverage of journalism on culture) have developed from cultural institutions with a primary focus on the common public interest, towards media institutions whose primary focus is commercial and media-professional. More specifically, contemporary cultural journalism in a continuum between culture, lifestyle and consumption is of considerable value and importance to the newspapers as media institutions. The individual newspapers, however, manage the form and content of their coverage of these subjects quite differently, according to their existing editorial profiles. Thus, cultural journalism is a subject of both shared editorial priority and differentiation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ubC44LjY5XzE